Estimating cumulative exposure of wildlife to non‐lethal disturbance using spatially explicit capture–recapture models. Issue 2 (February 2015) - Christiansen, Fredrik; Bertulli, Chiara G.; Rasmussen, Marianne H.; Lusseau, David
ABSTRACT: Impact assessments often focus on short‐term behavioral responses of animals to human disturbance. However, the cumulative effects caused by repeated behavioral disruptions are of management concern because these effects have the potential to influence individuals' survival and reproduction. We need to estimate individual exposure rates to disturbance to determine cumulative effects. We present a new approach to estimate the spatial exposure of minke whales to whalewatching boats in Faxaflói Bay, Iceland. We used recent advances in spatially explicit capture–recapture modeling to estimate the probability that whales would encounter a disturbance (i.e., whalewatching boat). We obtained spatially explicit individual encounter histories of individually identifiable animals using photo‐identification. We divided the study area into 1‐km 2 grid cells and considered each cell a spatially distinct sampling unit. We used capture history of individuals to model and estimate spatial encounter probabilities of individual minke whales across the study area, accounting for heterogeneity in sampling effort. We inferred the exposure of individual minke whales to whalewatching vessels throughout the feeding season by estimating individual whale encounters with vessels using the whale encounter probabilities and spatially explicit whalewatching intensity in the same area, obtained from recorded whalewatching vessel tracks. We then estimated the cumulative time whales spent with whalewatching boats to assess the biological significance of whalewatching disturbances. The estimated exposure levels to boats varied considerably between individuals because of both temporal and spatial variations in the activity centers of whales and the whalewatching intensity in the area. However, although some whales were repeatedly exposed to whalewatching boats throughout the feeding season, the estimated cumulative time they spent with boats was very low. Although whalewatching boat interactions caused feeding disruptions for the whales, the estimated low cumulative exposure indicated that the whalewatching industry in its current state likely is not having any long‐term negative effects on vital rates. © 2015 The Wildlife Society.